2019
DOI: 10.1177/1077559519829249
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic Development and Severe Parental Neglect in 4-Year-Old French-Speaking Children: ELLAN study

Abstract: Language is the most frequently compromised area of development in English-speaking neglected children, particularly the morphosyntactic component of language. This is very worrisome given its central role in academic success and social participation. No previous study has examined the morphosyntactic skills of French-speaking neglected children, despite the morphological richness of French. This study aimed to fill this gap. Forty-four neglected (mean age = 48.32 months, SD = 0.45) and 92 non-neglected (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Second, are these strategies adjusted to the developmental level of children exposed to neglect with MLU-Ds? Researchers have suggested that 4-year-old French-speaking children experiencing neglect show a level of morphosyntactic skills comparable to that of children as young as age 2 (Julien et al, 2019). The use of scaffolding strategies, for example, that elicit higher level language skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, are these strategies adjusted to the developmental level of children exposed to neglect with MLU-Ds? Researchers have suggested that 4-year-old French-speaking children experiencing neglect show a level of morphosyntactic skills comparable to that of children as young as age 2 (Julien et al, 2019). The use of scaffolding strategies, for example, that elicit higher level language skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, they displayed morphosyntactical skills similar to those of children as young as 2 (Julien et al, 2019). More specifically, their MLU, calculated in morphemes (MLU m ), appeared to be the most compromised indicator of other morphosyntactic skills, like word-omission errors or verbal inflections (Julien et al, 2019).…”
Section: Child Neglect and Language Developmentmentioning
confidence: 90%
See 2 more Smart Citations
“…Child neglect generally includes a lack of parental supervision, protection, and provision of basic needs such as nutrition, medical care, clothing, shelter, and education. Neglect may be physical, medical, educational, emotional (which includes a lack of affection and empathy), environmental, and supervisory (Julien et al, 2019;Morrongiello & Cox, 2020).…”
Section: Introductionmentioning
confidence: 99%